Implementation of Data-Driven Planning Through the Utilization of the Education Report Card at SMP Negeri Satap Paccerakang, Luwu Regency - Sitti Aminah; Asmanurhidayani Asmanurhidayani; Andi Tenriwaru (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study to analyze the Data-Based Planning (DBP) is a policy designed to improve the quality of educational planning through the utilization of educational data. However, the implementation of this policy at the school level still faces various challenges related to human resources, organizational culture, and technical support. This study aims to analyze the implementation of Data-Based Planning through the utilization of the Education Report Card at SMP Negeri Satap Paccerakang, Luwu Regency. The study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, school operator, and school supervisor. Data analysis used the interactive model of Miles, Huberman, and Saldaña, while the policy implementation analysis referred to George C. Edward III’s framework, which consists of communication, resources, disposition, and bureaucratic structure. The findings indicate that Data-Based Planning has been implemented through the utilization of Education Report Card data in preparing school programs and the School Activity and Budget Plan (RKAS). Communication and coordination regarding the policy have been carried out, although teachers’ understanding of educational indicators remains varied. Supporting factors include developing human resource competence, policy support, technological infrastructure, and a growing data-driven organizational culture. Inhibiting factors include limited data literacy, resistance to change, technical constraints, and administrative dependency. The study concludes that the implementation of Data-Based Planning has been running adequately but requires strengthening in data literacy, technical assistance, and organizational support to optimize educational planning and improve school quality.